DETERMINAN DAN SEBARAN KEJADIAN STROKE PADA LANSIA DI INDONESIA (ANALISIS DATA RISKESDAS 2018) - Meidy Wiradati, (2022)
Stroke is a disease with the second largest burden of morbidity after heart disease and is the cause of high disability rates worldwide. Generally, stroke can attack all age groups, but the elderly (≥55 years) show the largest stroke morbidity rate in Indonesia. The prevalence of stroke at age 55-64 years is 32.4 per-1000 population, age 65-74 is 45.3 per-1000 population, and age 75 years is 50.2 per-1000 population. This study aims to find out the factors associated with the incidence of stroke in the elderly in Indonesia. This study uses data from the 2018 Basic Health Research (Riskesdas) with a cross-sectional study design. The analysis used is the chi-square test and multiple logistic regression. The results of multivariate analysis showed that hypertension (p=0.000; POR=5.27; 95%CI 5.24-5.29), physical activity (p=0.000; POR=2.53; 95%CI 2.52-2 .54), gender (p=0.000; POR=2.35; 95%CI 2.33-2.36), employment status (p=0.000; POR=1.96; 95%CI 1.95-1 .97), diabetes mellitus (p=0.000; POR=1.70 95%CI; 1.69-1.71), smoking not every day (p=0.000; POR=1.15; 95%CI 1.14 -1,15), late elderly (p=0,000; POR=0,88; 95%CI 0,88-0,89), and consumption risk (p=0,000; POR=0,79; 95%CI 0, 79-0.80) has a relationship with the incidence of stroke in the elderly in Indonesia. This study concludes that hypertension is the most influential variable on the incidence of stroke in the elderly in Indonesia.